Contribution to organizational management by processes through sustentive process: ULEAM Tourism Observatory case - Espinoza Arauz, Mayra Yasmina; Zambrano Sornoza, Julaidy Dixiana; Juliana Margarita, Villaprado Lucas; Robert Antonio, Veliz Estacio (Journal of business and entrepreneurial studie, 2021)
It is emphasized that the current research was developed at the Tourist Observatory of the Laica Eloy Alfaro de Manabí University Uleam, in its Sucre extension located in the city of Bahía de Caráquez. The objective is to make a diagnosis of the internal processes developed by the Tourism Observatory of the Research Department, through observation practices aimed at demonstrating the procedures of this area of ??Uleam, ext. Bahía de Caráquez. This is a qualitative and quantitative research of a descriptive order, with the application of methods and techniques such as interviews and surveys. As a result, it was possible to know that this area is unknown by the students and about the processes that are developed due to the lack of organizational structure and management of the processes, in addition the students do not know how to be a voluntary member of it due to the lack of definition in writing and communication. The organizational structure of the institution by regulation is through Management by Processes to guarantee efficiency and effectiveness, which due to the recent creation of this area still lacks organizational elements. While the activities that are developed must be communicated so that it generates an impact on the community related directly and indirectly to the tourist activity for making timely and effective decisions in favor of the sustainability of their businesses.